Imaging dose from cone beam computed tomography in radiation therapy. Issue 7 (November 2015) - Alaei, Parham; Spezi, Emiliano
Abstract: Imaging dose in radiation therapy has traditionally been ignored due to its low magnitude and frequency in comparison to therapeutic dose used to treat patients. The advent of modern, volumetric, imaging modalities, often as an integral part of linear accelerators, has facilitated the implementation of image-guided radiation therapy (IGRT), which is often accomplished by daily imaging of patients. Daily imaging results in additional dose delivered to patient that warrants new attention be given to imaging dose. This review summarizes the imaging dose delivered to patients as the result of cone beam computed tomography (CBCT) imaging performed in radiation therapy using current methods and equipment. This review also summarizes methods to calculate the imaging dose, including the use of Monte Carlo (MC) and treatment planning systems (TPS). Peripheral dose from CBCT imaging, dose reduction methods, the use of effective dose in describing imaging dose, and the measurement of CT dose index (CTDI) in CBCT systems are also reviewed. Highlights: We review the available literature on imaging dose from cone beam CT in radiation therapy. We provide the range of doses from above procedure for different scan parameters. We review dose calculation methodologies. We review peripheral dose, effective dose, and dose reduction methodologies. We review CTDI measurements in CBCT systems.